2020
DOI: 10.1111/dme.14218
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characteristics of older people with type 1 diabetes treated with continuous subcutaneous insulin infusion or insulin injection therapy: data from the German/Austrian DPV registry

Abstract: Aim To compare clinical characteristics and outcomes in adults with type 1 diabetes aged ≥ 60 years using continuous subcutaneous insulin infusion (CSII) vs. insulin injection therapy. Further, to determine the percentage of older adults with type 1 diabetes using CSII.Research design and methods Retrospective study using data of the Diabetes Prospective Follow-up Registry (DPV). Including percentage CSII use from 2008 to 2018, and the characteristics of 9547 individuals extracted from the DPV in March 2019 (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…10 This risk-stratification approach encourages more complex treatment options, such as insulin pump therapy, for older adults who are considered low risk. Whilst several studies have highlighted insulin pump effectiveness amongst older adults with type 1 diabetes, 11 it is only recently that the first randomised trial of closed-loop automated insulin delivery exclusively studying older adults has been published. 1 This trial showed improvement in all prespecified continuous glucose monitoring (CGM) metrics with first-generation closed-loop delivery versus sensor-augmented pump therapy.…”
Section: Introductionmentioning
confidence: 99%
“…10 This risk-stratification approach encourages more complex treatment options, such as insulin pump therapy, for older adults who are considered low risk. Whilst several studies have highlighted insulin pump effectiveness amongst older adults with type 1 diabetes, 11 it is only recently that the first randomised trial of closed-loop automated insulin delivery exclusively studying older adults has been published. 1 This trial showed improvement in all prespecified continuous glucose monitoring (CGM) metrics with first-generation closed-loop delivery versus sensor-augmented pump therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Besonders bei Personen mit T1DM haben technische Lösungen wie Insulinpumpen und Glukosesensoren deutlich zugenommen (▶ Abb. 1a)[3,4], auch bei Patienten älter als 60 Jahre[5], während bei▶ Abb. 2 Schnellwirksame Insuline von 2000-2021.…”
unclassified
“…Notably, by combining the antenna and the filter in a single platform, this sensing device could measure glucose levels accurately regardless of the individual's characteristics, which is a great challenge for current glucose sensors in human trials. [ 201 ]…”
Section: Emergence Of On‐body Wearable Glucose Continuous Monitoringmentioning
confidence: 99%